Evaluation Of Internet Banking Service Quality For Customers Of BSI Bank KCP Yogyakarta Kusumanegara - Maulana Firmansyah; Nursya’bani Purnama (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to evaluate the quality of internet banking services at Bank Syariah Indonesia (BSI) KCP Yogyakarta Kusumanegara using five SERVQUAL dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. The object of the study was BSI KCP Yogyakarta Kusumanegara customers who use internet banking services, with a sample of 50 respondents selected through purposive sampling technique. This study used a quantitative method with data collection through questionnaires and analysis using descriptive statistics through the calculation of the average value (mean) to assess customer perceptions of each dimension of service quality. The results of the study indicate that in general the quality of BSI internet banking services has been running well in all dimensions, but tangible aspects still require evaluation and improvement, especially related to the interface display, design consistency, and ease of application access. The implications of this study emphasize the importance of optimizing the quality of internet banking services, especially in tangible aspects, so that BSI is able to provide superior, modern digital services that are in accordance with customer needs.